2021
DOI: 10.1098/rspb.2021.0399
|View full text |Cite
|
Sign up to set email alerts
|

The under-investigated wild side ofEscherichia coli: genetic diversity, pathogenicity and antimicrobial resistance in wild animals

Abstract: A striking paucity of information exists on Escherichia coli in wild animals despite evidence that they harbour pathogenic and antimicrobial-resistant E. coli in their gut microbiomes and may even serve as melting pots for novel genetic combinations potentially harmful to human health. Wild animals have been implicated as the source of pathogenic E. coli outbreaks in agricultural production, but a lack of knowledge surrounding the genetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 89 publications
2
28
1
Order By: Relevance
“…The role of wildlife and birds in the environmental spread of E. coli is poorly understood ( 58 ), but our high-resolution phylogenetic analysis shows at an unprecedented scale that some gST clones were shared between wildlife and the environment ( Fig. 3 ).…”
Section: Discussionmentioning
confidence: 94%
“…The role of wildlife and birds in the environmental spread of E. coli is poorly understood ( 58 ), but our high-resolution phylogenetic analysis shows at an unprecedented scale that some gST clones were shared between wildlife and the environment ( Fig. 3 ).…”
Section: Discussionmentioning
confidence: 94%
“…However, the STEC isolates reported in this study were mainly detected in wild non-sympatric animals raising questions about the real pathways of virulent bacteria spreading [ 51 ]. As previously suggested by other authors, the multi-virulent profiles observed in wild animals of MNP may be associated with the adaptation to the hosts rather than to the share of grazing land with livestock [ 52 ]. However, the pathogenic risk for endangered wild species or humans cannot be completely ruled out considering that some strains harboring virulence factors are also resistant to the antibiotics relevant for Public Health.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, E. coli are known to be able to carry virulence genes and share genetic information with its own and other bacterial species via horizontal gene transfer. Wild animals have been supposed to act as reservoirs of these virulence genes that aid pathogenesis but also as potential melting pots for novel gene combinations that could be more harmful to humans [ 22 ]. Therefore, investigations to verify the spreading of pathogenic E. coli in wildlife is pivotal in a One Health perspective.…”
Section: Discussionmentioning
confidence: 99%